2019
DOI: 10.4085/1062-6050-200-18
|View full text |Cite
|
Sign up to set email alerts
|

Concussion and National Hockey League Player Performance: An Advanced Hockey Metrics Analysis

Abstract: Context: Postconcussion deficits in neurocognitive performance and postural control may persist at the time of return to sport participation. How these deficits, if present, affect athletic performance is largely unknown, with prior studies showing mixed results.Objective: To evaluate postconcussion National Hockey League player performance using advanced hockey metrics over short-(5 games), medium-(10 games), and long-term (remainder of the season) seasonal performance.Design: Retrospective cohort study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…When compared with matched controls, players after a concussion demonstrated no statistically significant difference in short- and long-term performance. The maintained short-term performance revealed in our study corroborated the findings of Buckley et al, 3 who conducted a case series on the performance on 93 NHL players after concussion. The authors reported no difference in points per 60 minutes, Corsi percentage, Fenwick percentage, penalty difference, or PDO at 5 games, at 10 games, or for the remainder of the index season after concussion.…”
Section: Discussionsupporting
confidence: 91%
“…When compared with matched controls, players after a concussion demonstrated no statistically significant difference in short- and long-term performance. The maintained short-term performance revealed in our study corroborated the findings of Buckley et al, 3 who conducted a case series on the performance on 93 NHL players after concussion. The authors reported no difference in points per 60 minutes, Corsi percentage, Fenwick percentage, penalty difference, or PDO at 5 games, at 10 games, or for the remainder of the index season after concussion.…”
Section: Discussionsupporting
confidence: 91%
“…Their primary outcomes and performance indicators were similar to ours. Buckley et al 7 investigated the same cohort of injuries but used advanced hockey metrics in an attempt to detect more subtle metrics of player decline after injury; they included an expanded postinjury time frame (5 games, 10 games, and the remainder of the season) to detect more long-term effects of SRC. However, they also noted no deficits at any of the 3 time points after the return from injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also noted no deficits at any of the 3 time points after the return from injury. Buckley et al 7 explored a control group of players who missed time for noninjury reasons and determined that their postconcussion performance was similar to that of the control participants. Our results support the evidence from previous researchers that players did not experience performance deficits when returning to the NHL after an SRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 However, upon returnto-play some professional athletes have temporarily impaired sporting performance (e.g., adjusted plus-minus National Hockey League [NHL] scores and lower batting averages and decreased on-base percentages in Major League Baseball [MLB]) up to six weeks after sport-related concussion. 6,7 Many factors (e.g., psychological responses, medical care, and social support) [8][9][10] may influence athletes' time taken to return to their pre-injury level of sport competition, and then their sustained participation at pre-injury levels of sport competition after they have returned, following sport-related concussion. As such, it is important for many athletes who have sustained a sport-related concussion, and for their healthcare providers, to set a goal of returning to the same competitive level of sport to which the athlete was participating prior to injury.…”
Section: Introductionmentioning
confidence: 99%